Qualidade ambiental e situação da saúde no município de Bacabeira e nos municípios do entorno da Refinaria Premium I - Diniz, Rafaela Soares (2011)
The industry of I refinery of petroleum it is a great degrading of the environment, becayse she has potential of affect him in all the levels: air, water, soil and, consequently, the health of the you be alive. With the implantation of this enterprise, certainly the environmental quality of the resources and the health of the population of the municipal districts of the surroundings of the Refinery they will be affected direct and or indirectly. This research had as objective of the close municipal districts to the enterprise. A total 300 interviews was accomplished between the months of August and October of 2010, in the municipal districts of Bacabeira, Santa Rita and Rosário and in the rural places of the municipal district of São Luís: Estiva, Coqueiro and Vila Maranhão. For the collection of the data questionnaries were used semi-structured that were developed randomly with the population of the municipal districts and rural places involved in the research, the obtained data were stored in a database of the Program Excel 2007 so that they could be systematized and tabulated. The results demonstrated that in 62,0% of the interviewees in Santa Rita, 76% in Rosário, 40% in Vila Maranhão, they found the situation of the terrible health. The main diseases observed during the study they were the diseases of waterborne, and 34% of the intervewees in Coqueiro, 28% in Rosário, 52% in Santa Rita and 36% in Vila Maranhão, they already contracted primness. The form used for the "waste disposal" more found in the homes it was the septic sewage, 40% in Bacabeira, 42% in Coqueiro, 48% in Rosário , 50% in Santa Rita and 44% in Vila Maranhão. Most of the population doesn't know where the garbage is discarded, 46% in Bacabeira, 32% in Rosário, 42% in Santa Rita and 42% in Vila Maranhão. Most of the interviewees doesn't make any treatment type in the water, being naturally more exposed to the diseases. In relation to the perception of the interviewees' environment 81,3% they affirm that the environmental education is important, in relation to the climatic changes, 95,3% of the interviewees observed alterations in relation to the thermal sensation. Fifty-four percent of respondents in Bacabeira, 58% Coqueiro 74% in Rosario, in Santa Rita 60% and 70% in Vila Maranhão said that environmental degradation is worsening. The levels of pollutant stayed inside of the stablished patterns in the Resolução CONAMA nº03/90, not altering of this sorts out the quality of the air of the municipal districts. It is fundamental that are elaborated and made possible programs and monitoring politics and increment of the health and of the environmental resources, so that the operation of this enterprise doesn't swallow serious risks to the local resources and the health of the involved population.